Ssn6–Tup1 interacts with class I histone deacetylases required for repression - Watson, Anjanette D. (Cold Spring Harbor Laboratory Press, 2000)
Ssn6–Tup1 regulates multiple genes in yeast, providing a paradigm for corepressor functions. Tup1 interacts directly with histones H3 and H4, and mutation of these histones synergistically compromises Ssn6–Tup1-mediated repression. In vitro, Tup1 interacts preferentially with underacetylated isoforms of H3 and H4, suggesting that histone acetylation may modulate Tup1 functions in vivo. Here we report that histone hyperacetylation caused by combined mutations in genes encoding the histone deacetylases (HDACs) Rpd3, Hos1, and Hos2 abolishes Ssn6–Tup1 repression. Unlike HDAC mutations that do not affect repression, this combination of mutations causes concomitant hyperacetylation of both H3 and H4. Strikingly, two of these class I HDACs interact physically with Ssn6–Tup1. These findings suggest that Ssn6–Tup1 actively recruits deacetylase activities to deacetylate adjacent nucleosomes and promote Tup1–histone interactions.